INISIASI INTEGRATED FARMING SYSTEM (IFS) BAGI PETANI HORTIKULTURA DI DESA MAYANGAN, KECAMATAN GUMUKMAS KABUPATEN JEMBER - Azmi, Hilmi Tsabiatul; Putri, Widya Kristiyanti; Soeparjono, Sigit; Khozin, Mohammad Nur; Slameto (PAPUMA: Journal of Community Services, 2024)
The intensive farming system was still carried out by most farmers in Mayangan Village, Jember Regency, by implementing massive use of inorganic fertilizers. Thus, the activity has impacted the decrease in land quality and plant production. This community service aimed to educate farmers and initiate Integrated Farming System (IFS) in Mayangan Village. The community service was done for 6 months by steps; socializing, division work, practice, and evaluation. The community service was held in collaboration with the Ecophysiology of Tropical Plant Research Group (KeRis), University of Jember with farmers and livestock breeders from several farmer groups in Mayangan Village. The community service that has been carried out has made farmers more aware of the importance of integrated farming, especially the use of organic fertilizers in horticultural plant cultivation in Mayangan Village. This community service also increases cooperation between farmers and livestock breeders who collaborate to realize sustainable agriculture. Livestock waste can be processed into fertilizer, agricultural by-products can be used as animal feed, and during the process, soil fertility can be maintained properly, which is expected to increase the productivity of horticultural plants in Mayangan Village.